SISTEM REKOMENDASI PEMILIHAN PAKET INTERNET WIFI MENGGUNAKAN KNOWLEDGE BASED RECOMMENDATION - Laksono, Ardean Risqi; Nurmalitasari, Nurmalitasari; Irawan, Ridwan Dwi (ISTEK WIDURI, 2025)
The internet has become a crucial need in modern society, including in rural areas such as Wonokarto. PT. Yasmin Amanah Media, as a local internet service provider, offers a variety of internet packages to meet customer needs. However, the wide range of options often leads to confusion in selecting the most suitable package. This research aims to design a WiFi internet package recommendation system based on Knowledge-Based Recommendation (KBR) that can provide personalized suggestions based on user preferences. The system development method used is the System Development Life Cycle (SDLC), which consists of planning, analysis, design, implementation, testing, and maintenance phases. This study focuses on the system design stage in the form of a web-based application. Data were collected through interviews, observation, and literature study. The designed recommendation system utilizes constraint-based techniques to match user requirement attributes with the characteristics of available internet packages. The results show that the knowledge-based recommendation approach is effective in providing internet package selection suggestions, especially for new users who have no previous interaction history. This system is expected to improve customer satisfaction, internet usage efficiency, and loyalty to the services of PT. Yasmin Amanah Media.